Exploring strategies post- revocation of licensing exemption for Malaysia’s tailing processing industry - Muhammad Abdullah Rahmat,; Aznan Fazli Ismail,; Eli Syafiqah Aziman,; Nursyamimi Diyana Rodzi,; Ratnasuffhiyanni Omar,; Wan Mohd Razi Idris,; Tukimat Lihan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The extraction of heavy metals and rare-earth elements from tailing residue has caused a significant impact towards the environment as well as the industrial workers as a result from the contamination caused by the processing activities. The radionclide concentration of 226Ra, 232Th, and 40K in soil and tailing residue were found to be within the range of 0.31 - 4.97 Bqg-1 and 1.24 - 4.47 Bqg-1, 0.16 - 11.07 Bqg-1 and 1.08 - 8.56 Bqg-1, 0.22 - 1.24 and 0.18 - 1.32 Bqg-1, respectively. The radiological impack assessment findings indicated significant overexposure risks where the annual effective dose was estimated to be within the range of 0.7 – 207.6 mSvy-1 while the excess lifetime cancer risks we found to have exceeded the limit let by the local regulatory body. The correlation between study findings and the enactment of the licensing exemption order was done to identify the effects of non-regulatory compliance to the Atomic Energy Licensing Act. The study also emphasized on the remediation importance of industrial sites before implementing any form of changes towards new regulatory adherence. Hence, the study recommeneds potential remediation techniques but taking into account the operational status of each proceesing plant, degree of contation and possible future use of the contaminated site.